Dynamic conditional correlation and volatility spillover between conventional and Islamic stock markets: Evidence from developed and emerging countries - Mohammad Sahabuddin; Md. Aminul Islam; Mosab I. Tabash; Md. Kausar Alam; Linda Daniel; Imad Mostafa (Journal of Risk and Financial Management, 2023)
This study aims to investigate the dynamic conditional correlation and volatility spillover between the conventional and Islamic stock markets in developed and emerging countries in order to develop better portfolio and asset allocation strategies. We used both multivariate GARCH (MGARCH) and multi-scales-based maximal overlap discrete wavelet transform (MODWT) approaches to investigate dynamic conditional correlation and volatility spillover between conventional and Islamic stock markets in developed and emerging countries. The results show that conventional and Islamic markets move together in the long run for a specific time horizon and present time-varying volatility and dynamic conditional correlation, while volatility movement changes due to financial catastrophes and market conditions. Further, the findings point out that Chinese conventional and Islamic stock indexes showed higher volatility, whereas Malaysian conventional and Islamic stock indexes showed comparatively lower volatility during the global financial crisis. This study provides fresh insights and practical implications for risk management, asset allocation, and portfolio diversification strategies that evaluate stock market reactions to the crisis in the international avenues of finance literature.
Keywords: G10; G11; G15; G19; 650; conditional correlation; conventional and Islamic stock market; volatility spillover